JENIS DAN SERANGAN HAMA LALAT BUAH (Bactroceradorsalis) PADA TANAMAN TOMAT (Solanumlycopersicum.L) DI DESA TARAITAK KECAMATAN LANGOWAN UTARA KABUPATEN MINAHASA - Monalisa Debora Setlight; Elisabet. R. M. Meray; Maxi Lengkong (Universitas Sam Ratulangi, 2018)
ABSTRACT This study aims to determine: (1) the types of fruit flies that attack tomato plants and (2) the percentage of fruit fly attack Bactroceradorsalis on tomato plants in North LangowanSubdistrict, especially Taraitak Village.Â The time of the study was carried out for two months, from March to April 2019. The research was conducted using a survey method at several tomato planting locations inÂ NorthLangowan sub-district. Sampling using the diagonal slice method is to determine randomly where to pick tomatoes sampled which was attacked by Bactroceradorsalis. On land determined 5 points that are the location in determining the plants observed by adjusting the shape or area of tomato plants planted by farmers. Based on the results of the study it can be seen that the percentage of B. dorsalis fruit fly pests attack. on tomatoes every week is different. The first week was 11.21 percent, in the second week it increased to 12.18 percent.Â And in the third week also increased to 15.50 percent, then entered in the fourth week decreased to 9.08 percent and in the fifth week slightly increased to 9.44 percent. From the results of observations in the field of B. dorsalis fruit fly attack, the pests increased and decreased every week. Keywords : Fruit flies (Bactroceradorsalis), Tomato plants